2008
DOI: 10.2500/aap.2008.29.3114
|View full text |Cite
|
Sign up to set email alerts
|

Basophil activation test for the in vitro diagnosis of nonsteroidal anti-inflammatory drug hypersensitivity

Abstract: There is need for an in vitro diagnostic test for hypersensitivity to nonsteroidal anti-inflammatory drugs (NSAIDs). The purpose of this study was to assess the reliability of one such diagnostic, the basophil activation test. Forty-three drug hypersensitive patients referring several immediate reactions (anaphylaxis, urticaria, angioedema, asthma, and rhinoconjunctivitis) to one or more NSAIDs and 29 controls participated. Using the Basotest commercial kit, 63 determinations were performed with the drugs impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 18 publications
3
33
2
1
Order By: Relevance
“…This test is based on ASA-induced activation of basophils, followed by the measurement of the abundance of the CD63 surface marker. The results of previous publications conflict with those of some authors showing that ASA basophil testing is useful [14,15,16,17] and others showing that it is not [18,19]. Because of these conflicting results, we conducted a prospective single-blind study to evaluate the specificity of basophil responsiveness to ASA, as well as to diagnostically compare these results between clinically different patients and matched tolerant subjects.…”
Section: Introductioncontrasting
confidence: 43%
“…This test is based on ASA-induced activation of basophils, followed by the measurement of the abundance of the CD63 surface marker. The results of previous publications conflict with those of some authors showing that ASA basophil testing is useful [14,15,16,17] and others showing that it is not [18,19]. Because of these conflicting results, we conducted a prospective single-blind study to evaluate the specificity of basophil responsiveness to ASA, as well as to diagnostically compare these results between clinically different patients and matched tolerant subjects.…”
Section: Introductioncontrasting
confidence: 43%
“…18,19 CD203c can be rapidly measured by flow cytometry and has been proposed as a diagnostic tool in atopic disease, including peanut, drug and wasp venom allergy. [20][21][22] It has been shown that basophils are primed and hyper-responsive to Af allergen stimulation in CF-ABPA. 18 In this current study, BAT to Af was employed to identify Af sensitization in a CF cohort and it was correlated with key CF clinical measurements.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Based on the receiver operating characteristics-generated cutoff value of 17% for CD63-positive basophils, as captured by the usual anti-IgE-FITC method, Ebo et al [43] estimated a BAT sensitivity and specificity of 93.1 and 91.7%, respectively, as evaluated in a population of subjects allergic to latex, encouraging results that were then confirmed in subsequent reports by others [44]. Several reviews about this promising test began to appear, aimed at achieving possible acceptance while describing the state of the art of its application in allergy diagnosis [45,46,47,48,49,50,51], issues that are still being faced nowadays [52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74]. However, despite promising initial studies and some encouraging evidence, many authors agreed that CD63-based BAT remained disappointing in terms of sensitivity, while CD203c-based BAT showed a higher sensitivity (75 vs. 50%), though not as exciting as some reports suggested [39].…”
Section: The Use Of Basophil Flow Cytometry In Allergy Diagnosis: Stamentioning
confidence: 99%